Predictive model of growth kinetics for Staphylococcus aureus in raw beef under various packaging systems. (July 2020) - Yu, Hwan Hee; Song, Ye Ji; Kim, Yeon Jin; Lee, Hee Young; Choi, Yun-Sang; Lee, Na-Kyoung; Paik, Hyun-Dong
Abstract: This study describes a model of the growth kinetics for S. aureus in raw beef under wrapped packaging (WP), modified atmosphere packaging (MAP), vacuum packaging (VP), and vacuum skin packaging (VSP). Beef samples were inoculated with S. aureus and stored at 10, 15, 20, and 25 °C. VP and VSP showed lower maximum bacteria counts and higher lag time than WP and MAP at all temperatures. At 10 °C, S. aureus in VP and VSP decreased to about 2.5 Log CFU/g. Two primary models (modified Gompertz model and reparameterized Gompertz survival model) were used in the study. The secondary models were described using a polynomial equation and the Davey model. The bias factor (Bf), accuracy factor (Af), and root mean square error (RMSE) of the secondary models were 0.91–1.09, 1.00–1.13, and 0.00–0.68, respectively. The predictive models for kinetics of S. aureus in various packaged raw beef could help to predict the fate of S. aureus more accurately. Highlights: Predictive model for fate of S. aureus in various packaged raw beef was developed. The primary and secondary models of S. aureus growth were developed. The validation of predictive models (using Bf, Af, and RMSE) was carried out. Bf, Af, and RMSE were 0.91–1.09, 1.00–1.13, and 0.00–0.68, respectivley. Validation for secondary models were acceptable for describing of S. aureus .